PENGARUH PROMOSI DAN CITRAPERUSAHAAN TERHADAP KEPUASAN NASABAH (Studi Kasus PT. Asuransi Jiwasraya (persero) cabang Pekanbaru) - Naibaho, Adista Wikana; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Promotion is the seller of all the efforts made to introduce products to potential customers and persuade them to memebeli, and remind consumers long to make repeat purchases. With the promotion of good eating will enhance the positive corporate image of the service at the company, and can lead to the satisfaction of the customer. This research was conducted at PT. Insurance Jiwasraya (Persero) Pekanbaru branch in Jalan Sudirman No. yangberlokasi 341 Pekanbaru. The purpose of this research was conducted to analyze the effect of the promotion, corporate image on customer satisfaction. In this study the methodology used descriptively and quantitatively using SPSS, where samples diguankan that customers Jiwasraya Life Insurance. To determine the number of samples using the formula slovin. Data collection techniques using questionnaires and observation. Results of analysis using multiple linear regression, t test, and test fsehingga can be seen that the variable stress work negatively affects customer satisfaction (H1), that the company's image significantly influence customer satisfaction (H2), and the significant influence between promotion and corporate image of the customer satisfaction (H3).Keywords: Promotion, Corporate Image and Customer Satisfaction